The Association Between Smartphone Addiction, Learning Motivation Levels, and Cumulative Grade Point Average Among Students at the Faculty of Medicine, Pelita Harapan University - Purushotama, Nyoman Bagus Satcitta Ananda; Nainggolan, Julita Dortua Laurentina (Medicinus, 2025)
Background: Cumulative Grade Point Average (CGPA) is a crucial metric in higher education. Achieving a good CGPA increases students' opportunities for career advancement or further education. Smartphones can aid learning by boosting motivation and academic achievement but may also cause addiction when used primarily for entertainment. Objective: To examine the relationship between smartphone addiction, learning motivation levels, and CGPA among preclinical students at the Faculty of Medicine, Pelita Harapan University. Methodology: This cross-sectional analytical study involved 103 students with a minimum sample size of 95. Data were analyzed using SPSS version 23 through bivariate analysis. Results: Among the respondents, 70 students were addicted to smartphone use, 94 achieved satisfactory CGPA scores, and 65 had high learning motivation. A significant relationship was found between smartphone addiction and CGPA (p = 0.029), smartphone addiction and learning motivation (p = 0.013), and learning motivation with CGPA (p = 0.000). Conclusion: There is a significant association between smartphone addiction, learning motivation levels, and CGPA among students at the Faculty of Medicine, Pelita Harapan University.